Ligilactobacillus salivarius CNCM I-4866, a potential probiotic candidate, shows anti-inflammatory properties in vitro and in vivo - Carbonne, Celia; Chadi, Sead; Kropp, Camille; Molimard, Lise; Chain, Florian; Langella, Philippe; Martin, Rebeca (Frontiers in Microbiology, 2023)
The aim of this work was to characterize a new strain of Ligilactobacillus salivarius (CNCM I-4866) to address its potential as probiotic with a special focus on intestinal inflammation. Several in vivo and in vitro tests were performed in order evaluate the potential anti-inflammatory abilities of this strain and confirm its safety. Firstly, the strain was tested in a murine acute inflammation colitis model induced by DNBS. In vivo assay has shown a reduction of colonic damage and markers of inflammation after treatment with CNCM I-4866. Transcriptomic analysis performed on colons showed the capacity of the strain to down-regulate pro-inflammatory cytokines. In vitro experiments were thus performed to further analyze its mechanisms of action. L. salivarius CNCM I-4866 exerted anti-inflammatory profile by reducing IL-8 production by HT-29 TNF-α stimulated cell and modulated cytokines profile on peripheral blood mononuclear cells (PBMC). It protected intestinal integrity by increasing trans-epithelial electrical resistance (TEER) on Caco-2 TNF-α inflamed cells. Additionally, L. salivarius CNCM I-4866 displayed inhibition capacity on several intestinal pathogens and adhered to eukaryotic cells. Regarding safety and technical concerns, CNCM I-4866 was highly resistant to 0.3% of bile salts, produced mainly L-lactate, which is an interesting feature for patients with specific intestinal pathology. In addition, our strain was phenotypically sensitive to all antibiotics recommended by EFSA except for kanamycin. Finally, strain genomic characterization allowed us to confirm safety aspect of our strain, with no antibiotic gene resistance found. Taken together, these results indicate that L. salivarius CNCM I-4866 could be a good probiotic candidate for intestinal inflammation, especially with its steady anti-inflammatory profile.